Pendampingan Pengembangan Media Pembelajaran Sains Sekolah Dasar untuk Para Guru - Elisabeth Pratidhina Founda Noviani; Herwinarso Herwinarso; Jane Koswojo; Hady Sutris Winarlim (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2019)
A program to train Elementary School teacher in developing science learning media has been conducted in Dapena Elementary School and St Theresia II Catholic Elementary School, Surabaya. The training aims to improve teachers’ skills on making science learning media and teachers’ understanding on science concepts. In this training, teachers have made science learning media on the themes of air, electricity, and energy. According to pre- and post-test result analysis, teachers gain knowledge on scientific approach learning and science concept related to air, electricity, and energy themes. The calculated gain of average can be categorized as medium gain. In addition, according to the evaluation by participants, the program has been conducted very well.